Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To show that [tex]\(\log_{\frac{1}{a}} y = -\log_a y\)[/tex], we start with the definition of logarithms. By definition, if [tex]\(\log_b(y) = x\)[/tex], then [tex]\(b^x = y\)[/tex].
For the logarithm with the base [tex]\(\frac{1}{a}\)[/tex], we write:
[tex]\[ \log_{\frac{1}{a}} y = x \implies \left(\frac{1}{a}\right)^x = y \][/tex]
We know that [tex]\(\frac{1}{a} = a^{-1}\)[/tex], so we can rewrite the left-hand side:
[tex]\[ a^{-x} = y \][/tex]
By definition of the logarithm with base [tex]\(a\)[/tex], if [tex]\(a^z = y\)[/tex], then [tex]\(z = \log_a y\)[/tex]. Here, we have:
[tex]\[ a^{-x} = y \implies -x = \log_a y \implies x = -\log_a y \][/tex]
Therefore:
[tex]\[ \log_{\frac{1}{a}} y = -\log_a y \][/tex]
This property is now established.
Next, we use this property to solve the equation:
[tex]\[ \log_3(3 - x) = \log_{\frac{1}{3}}(5 - 2x) \][/tex]
Using the identity we just proved, we can rewrite the right-hand side:
[tex]\[ \log_3(3 - x) = -\log_3(5 - 2x) \][/tex]
Rewriting using the negative sign:
[tex]\[ \log_3(3 - x) = \log_3((5 - 2x)^{-1}) \][/tex]
Since the logarithms are equal, we can equate the arguments:
[tex]\[ 3 - x = (5 - 2x)^{-1} \][/tex]
Taking the reciprocal on both sides gives:
[tex]\[ (3 - x)^{-1} = 5 - 2x \][/tex]
Now, solving for [tex]\(x\)[/tex]:
1. Start with:
[tex]\[ \frac{1}{3 - x} = 5 - 2x \][/tex]
2. Cross-multiply to clear the fraction:
[tex]\[ 1 = (3 - x)(5 - 2x) \][/tex]
3. Expand the right-hand side:
[tex]\[ 1 = 15 - 6x - 5x + 2x^2 \][/tex]
[tex]\[ 1 = 15 - 11x + 2x^2 \][/tex]
4. Rearrange into standard quadratic form:
[tex]\[ 2x^2 - 11x + 15 - 1 = 0 \][/tex]
[tex]\[ 2x^2 - 11x + 14 = 0 \][/tex]
5. Solve this quadratic equation using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 2\)[/tex], [tex]\(b = -11\)[/tex], and [tex]\(c = 14\)[/tex]:
[tex]\[ x = \frac{11 \pm \sqrt{(-11)^2 - 4 \cdot 2 \cdot 14}}{2 \cdot 2} \][/tex]
[tex]\[ x = \frac{11 \pm \sqrt{121 - 112}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm \sqrt{9}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm 3}{4} \][/tex]
6. This gives two possible solutions:
[tex]\[ x = \frac{11 + 3}{4} = \frac{14}{4} = 3.5 \][/tex]
[tex]\[ x = \frac{11 - 3}{4} = \frac{8}{4} = 2 \][/tex]
Among these solutions, we need to verify which is valid for the original equation. Checking the valid solution:
For [tex]\(x = 3.5\)[/tex]:
[tex]\[ 3 - 3.5 = -0.5 \quad (\text{which does not work as log of a negative number is undefined}) \][/tex]
For [tex]\(x = 2\)[/tex]:
[tex]\[ 3 - 2 = 1 \quad \text{and} \quad 5 - 2(2) = 1 \quad (\text{valid}) \][/tex]
Thus, the valid solution is:
[tex]\[ x = 2 \][/tex]
For the logarithm with the base [tex]\(\frac{1}{a}\)[/tex], we write:
[tex]\[ \log_{\frac{1}{a}} y = x \implies \left(\frac{1}{a}\right)^x = y \][/tex]
We know that [tex]\(\frac{1}{a} = a^{-1}\)[/tex], so we can rewrite the left-hand side:
[tex]\[ a^{-x} = y \][/tex]
By definition of the logarithm with base [tex]\(a\)[/tex], if [tex]\(a^z = y\)[/tex], then [tex]\(z = \log_a y\)[/tex]. Here, we have:
[tex]\[ a^{-x} = y \implies -x = \log_a y \implies x = -\log_a y \][/tex]
Therefore:
[tex]\[ \log_{\frac{1}{a}} y = -\log_a y \][/tex]
This property is now established.
Next, we use this property to solve the equation:
[tex]\[ \log_3(3 - x) = \log_{\frac{1}{3}}(5 - 2x) \][/tex]
Using the identity we just proved, we can rewrite the right-hand side:
[tex]\[ \log_3(3 - x) = -\log_3(5 - 2x) \][/tex]
Rewriting using the negative sign:
[tex]\[ \log_3(3 - x) = \log_3((5 - 2x)^{-1}) \][/tex]
Since the logarithms are equal, we can equate the arguments:
[tex]\[ 3 - x = (5 - 2x)^{-1} \][/tex]
Taking the reciprocal on both sides gives:
[tex]\[ (3 - x)^{-1} = 5 - 2x \][/tex]
Now, solving for [tex]\(x\)[/tex]:
1. Start with:
[tex]\[ \frac{1}{3 - x} = 5 - 2x \][/tex]
2. Cross-multiply to clear the fraction:
[tex]\[ 1 = (3 - x)(5 - 2x) \][/tex]
3. Expand the right-hand side:
[tex]\[ 1 = 15 - 6x - 5x + 2x^2 \][/tex]
[tex]\[ 1 = 15 - 11x + 2x^2 \][/tex]
4. Rearrange into standard quadratic form:
[tex]\[ 2x^2 - 11x + 15 - 1 = 0 \][/tex]
[tex]\[ 2x^2 - 11x + 14 = 0 \][/tex]
5. Solve this quadratic equation using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 2\)[/tex], [tex]\(b = -11\)[/tex], and [tex]\(c = 14\)[/tex]:
[tex]\[ x = \frac{11 \pm \sqrt{(-11)^2 - 4 \cdot 2 \cdot 14}}{2 \cdot 2} \][/tex]
[tex]\[ x = \frac{11 \pm \sqrt{121 - 112}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm \sqrt{9}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm 3}{4} \][/tex]
6. This gives two possible solutions:
[tex]\[ x = \frac{11 + 3}{4} = \frac{14}{4} = 3.5 \][/tex]
[tex]\[ x = \frac{11 - 3}{4} = \frac{8}{4} = 2 \][/tex]
Among these solutions, we need to verify which is valid for the original equation. Checking the valid solution:
For [tex]\(x = 3.5\)[/tex]:
[tex]\[ 3 - 3.5 = -0.5 \quad (\text{which does not work as log of a negative number is undefined}) \][/tex]
For [tex]\(x = 2\)[/tex]:
[tex]\[ 3 - 2 = 1 \quad \text{and} \quad 5 - 2(2) = 1 \quad (\text{valid}) \][/tex]
Thus, the valid solution is:
[tex]\[ x = 2 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.